2017
DOI: 10.21834/e-bpj.v2i6.954
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Depression, Anxiety and Stress Among UiTM Dental Undergraduates in Clinical Years

Abstract: This study investigated the occurrence of depression, anxiety and stress; and identified the possible stress factors among clinical dental undergraduates. A cross sectional study was conducted among 127 dental undergraduates from Universiti Teknologi MARA (UiTM) Sungai Buloh, Malaysia. Overall the scores of DASS-21 shows majority of dental undergraduates have no depression, anxiety and stress. This study also highlights the main factor affecting the dental undergraduates' depression levels is the students' edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Recently, a sample of 326 participants was recruited from several urban communities in Malaysia and participants were assigned the DASS-21 and WHOQOL-BREF ( Farris et al , 2020 ). Similar to previous studies by Shamsuddin et al (2013) and Aziella et al (2017) , it was shown that anxiety had the highest prevalence (41.7%) among the participants. The sample was only drawn from urban communities because the authors presumed a higher prevalence of mental issues in urban settings ( Farris et al ., 2020 ).…”
Section: Introductionsupporting
confidence: 89%
“…Recently, a sample of 326 participants was recruited from several urban communities in Malaysia and participants were assigned the DASS-21 and WHOQOL-BREF ( Farris et al , 2020 ). Similar to previous studies by Shamsuddin et al (2013) and Aziella et al (2017) , it was shown that anxiety had the highest prevalence (41.7%) among the participants. The sample was only drawn from urban communities because the authors presumed a higher prevalence of mental issues in urban settings ( Farris et al ., 2020 ).…”
Section: Introductionsupporting
confidence: 89%
“…Contrary to the previous studies, quite a few studies found that female students had higher levels depression, anxiety and stress (21)(22)(23)(24)(25)(26). A study done among dental students by Mohd Nayan et al (27) however gave contradictory results to the previous studies that were discussed where majority of the students had no depression, anxiety or stress although there was a minority who reported severe levels of depression, anxiety and stress.…”
Section: Mental Health Disorders Amongst Dental Studentsmentioning
confidence: 84%
“…In addition, Malaysia is facing increasing psychological problems, such as depression, anxiety, and stress. 14 ' 15 Interestingly, researchers have reported that these mental health problems are significantly associated with smartphone addiction. 5 , 7 , 16 ' 17 The findings are consistent in studies in which smartphone addiction is associated with poor mental health status among university students.…”
Section: Introductionmentioning
confidence: 99%